Knowledge economy policy in Polish regions - Dariusz Woźniak; Justyna Sokołowska-Woźniak (European Regional Science Association (ERSA), 2012)
The aim of this paper is twofold. The first is to examine the level of development of knowledge economy in Polish regions (Voivodships). In order to assess the advances in building the knowledge economy in region, the composite indicator for years 2003-2008 is constructed. The second purpose is to analyse the regional authorities' policies directed towards supporting the pillars underlying the knowledge economy.
Keywords: 330